Renal vascular disparities among kidney donors presented at renal transplant unit- A single centre study - Lal, Naranjan; Hamid, Rashid Bin; Khan, Muhammad Tassaduq; Khan, Laraib (LIAQUAT MEDICAL RESEARCH JOURNAL, 2023)
Renal vasculature has been reported to show anatomical variations, which may lead to surgical complications. The pattern of renal vascular variations in Pakistani population is not well reported. Thus, this study was designed to assess the renal vascularity among kidney donors and correlate with age, gender and site of vessels. A total of 223 healthy volunteers underwent evaluation for kidney donation at the Radiology Department, DOW University Hospital, Karachi, Pakistan from January 2020 to July 2022 were included. The assessment of renal vasculature was done on computed (CT) angiogram. Renal vascular variations were found in 112 (50.2%), 59.8% were seen in males and 40.2% in females. On right side 50% vascular anomalies were found followed by left side with 27% and 22% on both sides. The arterial variants included accessory renal artery seen in 76 (67.8%) individuals, out of which 13.2% had in upper polar, 26.3% in hilum, 36.8% in lower polar, while 23.7% of early branching was observed. Ten retro-aortic, fourteen accessory renal veins and six bifurcation renal veins, along with six early branching renal veins, were present. Patient who received donor nephrectomy, the outcomes of the operation were completely consistent with the results of the CTA. According to this study, Pakistani population have differences in their renal venous and arterial anatomy, which can significantly influence surgical procedures.